2006
DOI: 10.1542/peds.2005-3123
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Associations Between Blood Lead Concentrations Lower Than 10 μg/dL and Neurobehavioral Development in Environmentally Exposed Children in Mexico City

Abstract: These analyses indicate that children's neurodevelopment is inversely related to their blood lead levels even in the range of < 10 microg/dL. Our findings were consistent with a supralinear relationship between blood lead levels and neurobehavioral outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
97
0
13

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(125 citation statements)
references
References 17 publications
11
97
0
13
Order By: Relevance
“…When considering memory, we also have to consider a cognitive function tightly related to language, negatively affected by the lead intoxication, as well as other cognitive functions, even when it is below 10 g/dl (3,8,9). The findings of the present study agree with the ones mentioned above, once it was found a considerable amount of damage in this function.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…When considering memory, we also have to consider a cognitive function tightly related to language, negatively affected by the lead intoxication, as well as other cognitive functions, even when it is below 10 g/dl (3,8,9). The findings of the present study agree with the ones mentioned above, once it was found a considerable amount of damage in this function.…”
Section: Discussionsupporting
confidence: 90%
“…Some authors suggest that even lower lead levels than the accepted by the World Health Organization present risk for disorders in the skills mentioned above, indicating that a security margin does not exist for lead exposure (3,(7)(8)(9). On the other hand, certain studies do not find correlation between the blood lead level and the neuropsychological dysfunctions presented by contaminated children, evidencing that genetic and environmental factors may aggravate the hindering effects of the lead in the neural development, making some children more vulnerable to the neurotoxic effects of the metal, or yet, despite having a significant influence in children's development, other environmental factors may be even stronger (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…2 Historical and recent research show that there is no safe exposure to lead in children without doing permanent and irreparable neurological, neurobehavioral, and physiological damage. [2][3][4][5][6][7][8][9][10][11][12][13] This damage may include a wide range of problems in children with the most common effect being permanent behavioral and learning deficits such as reduced IQ, ADHD, memory loss, etc. 2 Evidence of this irreparable damage led the Centers for Disease Control and Prevention (CDC) to lower the reference level (previously called the level of concern) for lead poisoning from ≥10 to ≥5 μg/dL in 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Se indica que todos los niños que viven en zonas reconocidas como de riesgo alto de intoxicación tengan pruebas de sangre y que sus niveles se mantengan bajo 10 µg/dL, porque varios estudios han demostrado alteraciones neurológicas y de conducta, aún a niveles más bajos que 10 µg/dL (9)(10)(11)(12) . En lugares de trabajo, el límite permisible promedio de plomo es 50 µg/m3 por la jornada de 8 horas (OSHA, Occupational Safety Health Administration, Department of Labor, Washington, DC).…”
Section: Absorción Del Plomounclassified